Effects of Dietary Protein to Lipid Ratio and Insect Meal on Growth Performance, Feed Utilization, and the Gut Microbiome of Lake Whitefish (Coregonus clupeaformis) - Rebecca Lawson; Yubing Chen; Junyu Zhang; Marcia A. Chiasson; Jennifer Ellis; Dominique Bureau; Richard D. Moccia; David Huyben (Aquaculture Nutrition, 2025)
Wild stocks of lake whitefish (Coregonus clupeaformis) are declining in the Great Lakes, and there is a lack of information on their nutritional requirements and gut health indicators to effectively culture them in an aquaculture setting. The aim of this study was to evaluate the growth performance, nutrient utilization, and gut microbiome of lake whitefish fed varying protein:lipid ratios with and without the inclusion of insect meal from black soldier fly (BSF). In total, 450 lake whitefish (301 ± 10 g) were fed one of five diets with differing protein-to-lipid ratios (high-protein 54%, low-protein 48%, high-lipid 18%, or low-lipid 12%), and an additional commercial control rainbow trout diet (Bluewater commercial control [BCC]). High-protein diets included 5% BSF meal to explore its potential to partially replace fishmeal in the diet. After 16 weeks at 8.5°C, growth performance and nutrient digestibility were the highest for lake whitefish fed the high-protein–high-lipid (HPHL) and BCC diets, while the feed conversion ratio (FCR) was numerically lowest for the HPHL. Protein and energy retention, and lipid digestibility were highest for fish fed the HPHL and BCC diets, while the BCC diet had the highest lipid retained, concomitant with high viscerosomatic index (VSI). High lipid in fish, especially in the viscera that is removed during processing, is not desirable, thus the HPHL diet is recommended. The gut microbiome was dominated by Proteobacteria, specifically by the genera of Shewanella and Aeromonas, although feeding high-lipid diets resulted in the lowest alpha diversity, but was not significant. These results are novel for this species, and we recommend that lake whitefish diets should be formulated to have a minimum 54:18 protein-to-lipid ratio. The results from this study provide baseline information on the nutrition and gut microbiome of lake whitefish, which can be used to develop a species-specific feed rather than feeding them rainbow trout feed. However, further work on targeted breeding and genetic selection of broodstock, together with diet optimization, is needed to improve the growth performance and nutrient utilization in order to enable an effective, economical, and environmentally sustainable culture of lake whitefish.